Film Dokumenter Talempong Sungai Pua - Iqbal Maulana Irsyadi; Defrizal Saputra (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
The Talempong River craft is located in the West Sumatra region, l. Lukok No.125, Sungai Pua, Kec. Pua River, Agam Regency, West Sumatra province. The Talempong Sungai Pua craft does not yet have documentation starting from history, the beginning of the founding of the Talempong Sungai Pua craft and others which make people unaware of the unique history. The design of this documentary film aims to collect various explanations that can be seen by the public, especially the millennial generation, early communities or people living outside West Sumatra who want to know about this craft. The design of the film uses the 4D method which consists of 4 stages, namely define, design, develop, and disseminate. The data analysis method used in this final work is the 5w+1h method. Taking the object of the Pua River talempong craft, there is no history that has been filmed and not many people know about the history, production or what the talempong craft is, in the form of a documentary film, everything is summarized, this documentary film will later be of interest to both historians and the public. laypeople, the millennial generation have minimal knowledge about the history and production methods of Talempong Sungai Pua crafts and want to know the history and uniqueness of crafts.